Relating sustainable development goals in a conceptual integrated model of growth and welfare - Karina Simone Sass; Tomaz Ponce Dentinho (REGION, 2023)
The United Nations Sustainable Development Goals (SDG) is one of the most relevant efforts aiming at the promotion of sustainable development around the world. Many indicators serve as a guide to evaluate the actual level of development and to identify the issues that need more attention. What is not clear yet is the association between the goals and their indicators. This can limit the information on effective political tools to reduce inequalities at the national and local levels. Based on that, the paper aims to explore the connections between SDGs. Its approach involves i) the proposal of a conceptual integrated model of sustainable development rooted in the literature and connectable with the SDGs; ii) based on World Bank (2019) data on sustainable indicators over two decades, the test of a two-stage econometric model, one to explain product per capita and a second one to explain lack of happiness, assessed by the suicide rate. From the results, it is possible to identify the factors that influence the level of wealth and happiness while integrating Sustainable Development Goals.
Keywords: I3; Q01; C23; 330; Sustainable Development Goals; Sustainable Growth Model; Happiness; SDG indicators